Luto antecipatório: intervenção de enfermagem para o cuidador familiar de pacientes em cuidados paliativos à luz da teoria da tristeza crônica - Fernandes, Maria Andréa (2021)
Introduction: palliative care is an approach aimed at symptom control, comfort and quality of life. It is offered in conjunction with the standard treatment of any illness that threatens the continuity of life and offers a support system to help the family to deal with the patient's illness and in the anticipatory mourning process. This thesis consisted of three articles: one theoretical and two originals. Methodology: the proposed study was conducted in three stages: the first was a reflective study, developed through the investigation of the Chronic Sadness Theory and its application in nursing practice focused on care in the process of anticipatory grief in the context of Palliative Care. In the second stage, a methodological study was carried out and followed the following operational phases: initial translation, synthesis of translations, back-translation, evaluation of documents by the Expert Committee and a pre-test carried out with 30 family caregivers of patients under Palliative Care. In the third stage, a field research with a qualitative approach was carried out. Data collection took place from January to March 2020, with ten family caregivers, from a nursing intervention with therapeutic completion letters. The research protocol was approved by a Research Ethics Committee, under opinion number 3,787,780. The empirical material was categorized using Bardin's content analysis technique and analyzed in the light of the Chronic Sadness Theory. Results: the first study highlighted that the Chronic Sadness Theory is predictive in terms of scope. Metaparadigm concepts have significance, internal consistency, and are operable. The theory is parsimonious, can be used by nurses and is aimed at people with chronic diseases in the final stage of life and their family caregivers. In the second manuscript, the Content Validity Coefficient values were satisfactory in relation to 'Language clarity' (0.94), 'Theoretical relevance' (1.00), 'Theoretical relevance' (0.99) and the Theoretical dimension, whose degree of agreement was excellent (kFleiss=0.789). For most respondents, the items listed were understood and presented clarity. The psychometric qualities of the instrument were satisfactory and applicable to family caregivers of patients under palliative care. In the third manuscript, from the participants' reports, four thematic categories emerged: 'Valuing the family caregiver', 'Providing the family's affective bond', 'Strengthening the therapeutic relationship' and 'Effective coping strategies'. It was observed that the care provided by the nurse contributed to the caregiver to develop their individual growth and spiritual maturation, to build unique relationships with their loved ones and with other family members, that the therapeutic letters are applicable to the caregiver and had positive effects. Final reflections: the use of therapeutic letters enabled the nurse to provide effective care, alleviating chronic sadness in the anticipatory mourning process in the context of Palliative Care, adequately supporting the family member in their role as caregiver. The findings evidenced in the literature corroborate the results of this study and reinforce the use of the Theoretical Model of Chronic Sadness to support the practice of palliative nursing for the planning of holistic care. It is hoped that the data obtained can support further investigations on the subject.